1994
DOI: 10.1093/jac/33.5.1005
|View full text |Cite
|
Sign up to set email alerts
|

Significant reduction in chloroquine bioavailablity following coadministration with the Sudanese beverages Aradaib, Karkadi and Lemon

Abstract: Chloroquine bioavailability in healthy males was examined following oral coadministration of 600 mg with three common Sudanese beverages, Aradaib (Tamarindus indica), Karkadi (Hibiscus sabdarifa) and Lemon (Citrus limetta) and drinking water. The tablets and beverages were taken on an empty stomach after an overnight fast. The plasma chloroquine concentrations were measured by HPLC. The extent and rate of chloroquine bioavailability were described by the area under the plasma concentrations versus time curve (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 6 publications
2
24
0
Order By: Relevance
“…However, in vivo tests are affected by variables that might be out of control such as absorption deficit due to the diet (Tulpule & Krishanaswamy 1982, 1983, McElnay et al 1982, Romero et al 1993 or other drugs (Mahmoud et al 1994), increased degradation of the drug into inactive metabolites and presence of intestinal parasite infections. We found prevalence of intestinal parasite infections in all age groups and rural and urban areas in around 50% of individuals (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo tests are affected by variables that might be out of control such as absorption deficit due to the diet (Tulpule & Krishanaswamy 1982, 1983, McElnay et al 1982, Romero et al 1993 or other drugs (Mahmoud et al 1994), increased degradation of the drug into inactive metabolites and presence of intestinal parasite infections. We found prevalence of intestinal parasite infections in all age groups and rural and urban areas in around 50% of individuals (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…10 Changes in gastric acidity and motility or the delay of gastric emptying may slow absorption of CQ, as these changes will prolong the duration of time that the drug remains in the stomach. 3,26 Finally, increased diuresis is often reported among khat chewers, possibly due to fluid intake during khat-chewing sessions; 26 this may lead to increased urinary excretion of CQ. Other possible mechanisms of pharmacokinetic interactions between khat and CQ require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Drug-food, drug-drug and drug-herb interactions are factors that can alter the pharmacokinetic activity of a drug; these interactions can occur during absorption, distribution, metabolism or excretion. 7 Catha edulis of the Celastraceae family, also known as khat, is a plant widely cultivated in East Africa (e.g.…”
mentioning
confidence: 99%
“…Prior clinical studies reported a decrease in the terminal half-life of acetaminophen without a significant corresponding change in AUC and clearance (Kolawole and Maduenyi, 2004); a reduction in the metabolic clearance of diclofenac (Fakeye et al, 2008) and a reduction in the bioavailability of chloroquine (Mahmoud et al, 1994) when these drugs were administered concomitantly with the extracts of H. sabdariffa. These drugs are metabolised by more than one CYP isoform: acetaminophen is metabolised by CYP isoforms 1A2, 2A6, 2D6, 2E1 and 3A4 (Patten et al, 1993); diclofenac by CYPs isoforms 2C9 and 3A4 (Tang et al, 1999) and chloroquine is metabolised by CYP2C8, 2D6 and 3A4/5 (Ducharme and Farinotti 1996; Kim et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that it can be used in the treatment of hypertension and it has actually been shown to have antihypertensive effect comparable to captopril, in man (Odigie et A common practice in some part of the world is the use of juices, sodas and sometimes herbal drinks such as the water beverage of Hibiscus sabdariffa (Zobo) to administer drugs (Huang & Lawrence 2004;Fakeye et al, 2007). The water extract of Hibiscus sabdariffa caused a reduction in the elimination of acetaminophen and diclofenac and also a reduction in the bioavailability of chloroquine (Mahmoud et al, 1994;Fakeye et al, 2007;Kolawole and Maduenyi, 2004). The mechanism responsible for this pharmacokinetic herb-drug interaction has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%